Rekrutmen Box Mussel, Septifer Bilocularis L. Efek Substratum Dan Kepadatan Dewasa - Medy Ompi (Masyarakat Moluska Indonesia, 2019)
An intertidal population of Septifer bilocularis L. was studied in Tongkeina, North Sulawesi, Indonesia. Open and closed cages were applied in field experiments to study the effects of four types of substrata on settling of S. bilocularis: live shells of adults, dead shells, coral rubble, and sand. Each substratum was tested with four levels of adult mussel density: 0, 10, 50, 100 individuals per compartment. The number of recruits as a function of cage, substratum, and adult density was analysed using Two-way ANOVA. The experiment showed that new recruits were affected by the substratum but not by the density of adults. The surface of adult box mussels was the most attractive substratum for recruits